Gastric Metastasis from Ovarian Adenocarcinoma Presenting as a Submucosal Tumor without Ulceration (Gut and Liver, 2009)
Metastatic gastric cancer is extremely rare and gastric metastasis from ovarian adenocarcinoma has rarely been reported. All of the previously reported metastatic lesions presented as an ulcerative lesions. We report a case of 49-year-old woman in which gastric metastasis from ovarian adenocarcinoma presented as a submucosal tumor without ulceration on endoscopic examination. Gastrointestinal stromal tumor was suspected on endoscopic ultrasound (EUS) examination. It was confirmed histopathologically as metastatic ovarian adenocarcinoma after endoscopic submucosal dissection (ESD) with enucleation. Submucosal tumor of the stomach in patients with ovarian carcinoma should not be overlooked and ESD with enucleation may be a viable option when EUS with fine needle aspiration is not available.